Gender Issues in Application of Islamic Law in Nigeria - Muhammad S. Umar (Al-Jami'ah: Journal of Islamic Studies, 2007)
This essay explores gender issues in the contemporary application of Islamic law in the Muslim majority-states of northern Nigeria. Brief political background helps to explain the shari‘a codes enacted by the legislatures of the states, drawing largely from the classical formulations of Maliki school of Islamic law. Women were among the first to be prosecuted and sentenced to death by stoning for the offence of zinā. To provide effective legal defense for the accused women, their lawyers and activists for women human rights had to argue in Islamic law before they could convince Shari‘a Courts of Appeal to overturn the sentences of death by stoning and set the women free. In the process, women activists learned a lot about the classical formulations of Maliki school of Islamic law, where they discovered the rich flexibility of Islamic thought, and that has empowered them to articulate Islamic criticisms against gender bias in the recently enacted shari‘a codes.